PENGEMBANGAN MEDIA PEMBELAJARAN PUZZLE PADA MATERI PECAHAN KELAS IV SD - Gini Lailatul Isnaini; Nora Surmilasari; Jayanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Fraction puzzle media is one type of mathematics learning media. The problems in this study are: 1) How valid is puzzle learning media for fraction material in fourth grade elementary school? 2) How practical is puzzle learning media for fraction material in fourth grade elementary school? 3) How effective is puzzle learning media for fraction material in fourth grade elementary school? In this study, the type of research used is development research (R&D) with the ADDIE model. The data collection techniques used in this study are observation, questionnaires, tests, and documentation. In this study, the validation techniques used are expert validation of media, material, and language. The data analysis technique in this study is from each data collected, consisting of analysis of the results of expert validation. This study yielded results from expert validation of media, content, and language, achieving a percentage of 93.33%, which is categorized as highly valid. From the practicality aspect, the results of the One-to-One pilot test questionnaire achieved a percentage of 93.33%, categorized as highly practical, and the Small Group pilot test achieved a percentage of 93.34%, also categorized as highly practical.